Immunogenicity of COVID‐19 vaccines in patients with diverse health conditions: A comprehensive systematic review. Issue 9 (27th May 2022) - Cho, Kyuyeon; Park, Seoyeon; Kim, Eun‐Young; Koyanagi, Ai; Jacob, Louis; Yon, Dong K.; Lee, Seung Won; Kim, Min Seo; Radua, Joaquim; Elena, Dragioti; Il Shin, Jae; Smith, Lee
Abstract: It remains unclear how effective COVID‐19 vaccinations will be in patients with weakened immunity due to diseases, transplantation, and dialysis. We conducted a systematic review comparing the efficacy of COVID‐19 vaccination in patients with solid tumor, hematologic malignancy, autoimmune disease, inflammatory bowel disease, and patients who received transplantation or dialysis. A literature search was conducted twice using the Medline/PubMed database. As a result, 21 papers were included in the review, and seropositivity rate was summarized by specific type of disease, transplantation, and dialysis. When different papers studied the same type of patient group, a study with a higher number of participants was selected. Most of the solid tumor patients showed a seropositivity rate of more than 80% after the second inoculation, but a low seropositivity was found in certain tumors such as breast cancer. Research in patients with certain types of hematological malignancy and autoimmune diseases has also reported low seropositivity, and this may have been affected by the immunosuppressive treatment these patients receive. Research in patients receiving dialysis or transplantation has reported lower seropositivity rates than the general population, while all patients with inflammatory bowel disease have converted to be seropositive. Meta‐analysis validating these results will be needed, and studies will also be needed on methods to protect patients with reduced immunity from COVID‐19.